Evaluation of Earth Dam Leakage Considering the Uncertainty in Soil ‎Hydraulic Parameters - Mohammad Reza Boroomand; Amirhossein Mohammadi (Civil Engineering Journal, 2019)
Analysis of earth dams is generally conducted in three stages of stability, deformability and water penetration analysis. Lack of sufficient attention to leakage, as one of the most important issues, leads to erosion and destruction of slope stability. The aim of current paper is to analyze the earth dam leakage with respect to the existing uncertainty in soil hydraulic parameters. In this research, the Monte Carlo (MC) method was used to calculate soil hydraulic parameters. Using these parameters, analysis of Alborz earth dam leakage by means of SEEP/W model based on the finite elements method was investigated. Due to the hydraulic conditions of the core soil, the total head value, pore water pressure, and water flux in core region will change. The results indicate that uncertainty in the hydraulic parameters of Alborz earth dam are significant, thus risk is important in this dam. The application of the proposed methodology in estimation of leakage from Alborz earth dam in Mazandaran province reveals its efficiency and proper accuracy in predicting the amount of leakage flow in earth dams with respect to the possible changes in the hydraulic parameters of the soil. Moreover, it was found that the quantity of seepage increases considerably when the dam is without core, therefore, the core is very necessary to decrease the value of seepage through the earth dam.